Web Usage Mining, Pattern Discovery dan Log File - Suratno, Tri; Prahasto, Toni; Rochim, Adian Fatchur (Universitas Diponegoro, 2011)
Analysis of data to access the server can provide significant and useful information for performance improvement, restructuring andimproving the effectiveness of a web site. Data mining is one of the most effective way to detect a series of patterns of information from large amounts of data. Application of data mining on Internet use called web mining is a set of data mining techniques are used for the web. Web mining technologies and data mining is a combination of web, which is the integration of technology resources extracted from the information world wide web as the implications of the web resources of interest to know the value of the model extraction Potentialuse of data mining algorithms over a variety of observational data for identify patterns of web resources. Target analysis of web mining is the data from the web, such as data visitors access, web page structure, and format web pages. Target analysis of the study is that web mining web usage mining using association rules on the website www.faperta.unja.ac.id obtained from the log file that is used to discover the navigation patterns, and discover the rules of the association between a combination of items. To determine the pattern ofvisits in a web, and to identify what pages are frequented by visitors of a website, which can be used to improve website design andrecommend the display, as well as the links are often used by visitors, so the quality of services from website www.faperta.unja.ac.id can be provided effectively and efficiently.Keywords : Web Mining; Web usage mining; Data mining; Log file; Website; World wide web